A decision support framework for grading of civil engineering contractors and evaluation of infrastructure project performance - Chiloane-Nwabueze, Salome (University of the Witwatersrand, Johannesburg, 2024)
The construction sector plays a key role in the economic development of a country. The management of this sector is thus crucial in maximising the performance of the sector and the economy. The South African construction sector performance has some level of inefficiencies that could be improved to enhance the sector’s performance outputs. Therefore, the study aimed to develop a framework for grading civil engineering contractors and the evaluation of project performance. To achieve this, the study reviewed the literature on relevant key concepts and CIDB processes and systems. The government of South Africa has mandated the registration and grading of contractors to the Construction Industry Development Board (CIDB). The CIDB grade is a license for trading with the government. It certifies contractors who are graded as capable of delivering projects up to a pre-determined contract value in each class of work. Currently, the grading system is based on two key determinants, which are the contractor’s track record (i.e., completed projects) and available capital. Presently, a contractor grade does not denote the contractors’ capabilities. However, contractor grading and performance evaluation should be a multi-criteria decision-making process. A questionnaire was developed and distributed to the key participants in the industry to establish whether there is a need for enhancing the current registration, grading, and performance evaluation of contractors in the construction sector and to establish relevant criteria. Of the 149 respondents, the results of the study have revealed that most of the respondents (88.6%) agree that enhancing the current construction sector entry requirements could assist in improving contractors’ capabilities. Moreover, 90.6% of the respondents have indicated that enhancing the current construction sector entry requirements will assist in improving the performance outputs of the construction sector. A multicriteria decision-making methodology using the Analytical Hierarchy Process (AHP) based on seven main criteria with seventeen sub-criteria was carried out for iii grading of contractors and performance evaluation of contractors. Thereafter, using the results obtained from the AHP, an enhanced framework was developed for registering, grading, and evaluating the performance of contractors. Relevant scenarios and CIDB grading scenarios were applied to test and validate the developed framework. The construction sector entry requirements have been proposed by the study based on the literature reviewed and results of the state of practice survey to improve the sector performance. One way of improving the sector’s performance is through entry regulation. Organisations and some countries worldwide have some form of entry regulation to manage the construction sector. To minimise business failure and poor performance, new entrants need to have at least a recognised technical qualification in the aspiring field of work. This will ensure that new entrants have the relevant knowledge of the field in which they aspire to enter. Having entry regulations and improved grading and performance evaluation systems may assist in improving the sector’s performance. Proposals on the enhancements that may be considered by the CIDB are made which may assist in improving the industry’s performance.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Engineering and the Built Environment , School of Civil and Environmental Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Construction Sector; Grading System; Multi-criteria Decision Making; Analytical Hierarchy Process; Construction Industry Development Board; SDG-8: Decent work and economic growth